(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
Chile will soon have a new Constitution. 78.27% of the people who voted in the referendum last October 25 expressed their final opinion in this direction. A Constituent Assembly composed of 155 citizens identified exclusively by popular vote from next April 11 will have the task of drafting the constitutional text. However, even though the referendum recorded the highest turnout since the return to democracy, the rate of abstention remained high even in this circumstance. In fact, around 49% of those eligible did not go to vote on this occasion either. This seems to confirm the ever wider rift that has arisen between the traditional political class and the electorate, the reasons for which appear to be structural, deeply rooted and long-standing.